Decreased MARCKS Protein Expression in Kidney Cortex Membrane Fractions of Cathepsin B Knockout Mice Is Associated with Reduced Lysophosphatidylcholine and Protein Kinase C Activity - Tamim Kawakibi; Niharika Bala; Lauren P. Liu; Louis A. Searcy; Nancy D. Denslow; Abdel A. Alli (Biomedicines, 2023)
Cathpesin B is a multi-functional protease that plays numerous roles in physiology and pathophysiology. We hypothesized that actin cytoskeleton proteins that are substrates of cathepsin B, various lipids, and kinases that are regulated by lipids would be down-regulated in the kidney of cathepsin B knockout mice. Here, we show by Western blot and densitometric analysis that the expression and proteolysis of the actin cytoskeleton proteins myristoylated alanine-rich C-kinase substrate (MARCKS) and spectrin are significantly reduced in kidney cortex membrane fractions of cathepsin B knockout mice compared to C57B6 wild-type control mice. Lipidomic results show that specific lipids are increased while other lipids, including lysophosphatidylcholine (LPC) species LPC (16:0), LPC (18:0), LPC (18:1), and LPC (18:2), are significantly decreased in membrane fractions of the kidney cortex from Cathepsin B null mice. Protein Kinase C (PKC) activity is significantly lower in the kidney cortex of cathepsin B knockout mice compared to wild-type mice, while calcium/calmodulin-dependent protein kinase II (CaMKII) activity and phospholipase D (PLD) activity are comparable between the two groups. Together, these results provide the first evidence of altered actin cytoskeleton organization, membrane lipid composition, and PKC activity in the kidneys of mice lacking cathepsin B.